KAJIAN HUKUM TERHADAP PERKAWINAN BEDA AGAMA DENGAN ADANYA YURISPRUDENSI MAHKAMAH AGUNG NO. 1400K/PDT/1986 - Karina Lizwary; Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2016)
Indonesia as pluralistic country with assorted tribe, race, language and culture and religion so that intermarriage occurs frequently. Intermarriage itself is not regulated in Law No. 1 of 1974 on Marriage and with the jurisprudence of the Supreme Court No. 1400 K / PDT / 1986 in the Jurisprudence decision does not prohibit the intermarriage so that the terms of a marriage is no longer an obstacle for those who want to perpetuate Interfaith Marriage. The issue of interfaith marriage arises in our country as a logical consequence of the recognition of Pancasila as the foundation of legal product, which contained therein "The principle of religion freedom", so long as we continue to recognize the existence of these two things, the issue of interfaith marriage will always appear, therefore how records of a marriage which has rules that are different and what is contained in the jurisprudence, in consideration of a judge.